Imaging of Transmetallation and Chelation Phenomena Involving Radiological Contrast Agents in Mineral-Rich Fruits - Subhendra Sarkar; Zoya Vinokur; Bleidis Buitrago; Lin Mousa; Hayley Sanchez; Analia Basilicata; Jodi-Ann Douglas; Seanetta Reddock (Tomography, 2022)
Exogenous heavy metals or non-metallic waste products, for example lanthanide or iodinated contrast media for radiological procedures, may interfere with the biochemical pools in patients and in common food sources, creating an excess buildup of exogenous compounds which may reach toxic levels. Although the mechanisms are unknown, our experiments were designed to test if this toxicity can be attributed to “transmetallation” or “chelation” reactions freeing up lanthanides or chelated transition metals in acidic fruits used as phantoms representing the biologically active and mineral-rich carbohydrate matrix. The rapid breakdown of stable contrast agents have been reported at a lower pH. The interaction of such agents with native metals was examined by direct imaging of contrast infused fresh apples and sweet potatoes using low energy X-rays (40–44 kVp) and by magnetic resonance imaging at 1.5 and 3T. The stability of the exogenous agents seemed to depend on endogenous counterions and biometals in these fruits. Proton spin echo MR intensity is sensitive to paramagnetic minerals and low energy X-ray photons are sensitively absorbed by photoelectric effects in all abundant minerals and were compared before and after the infusion of radiologic contrasts. Endogenous iron and manganese are believed to accumulate due to interactions with exogenous iodine and gadolinium in and around the infusion spots. X-ray imaging had lower sensitivity (detection limit approximately 1 part in 104), while MRI sensitivity was two orders of magnitude higher (approximately 1 part in 106), but only for paramagnetic minerals like Mn and Fe in our samples. MRI evidence of such a release of metal ions from the native pool implicates transmetallation and chelation reactions that were triggered by infused contrast agents. Since Fe and Mn play significant roles in the function of metalloenzymes, our results suggest that transmetallation and chelation could be a plausible mechanism for contrast induced toxicity in vivo.